Phishing exposed - James, Lance (Syngress, 2005)
Phishing Exposed unveils the techniques phishers employ that enable them to successfully commit fraudulent acts against the global financial industry. Also highlights the motivation, psychology and legal aspects encircling this deceptive art of exploitation. The External Threat Assessment Team will outline innovative forensic techniques employed in order to unveil the identities of these organized individuals, and does not hesitate to remain candid about the legal complications that make prevention and apprehension so difficult today. This title provides an in-depth, high-tech view from both sides of the playing field, and is a real eye-opener for the average internet user, the advanced security engineer, on up through the senior executive management of a financial institution. This is the book to provide the intelligence necessary to stay one step ahead of the enemy, and to successfully employ a pro-active and confident strategy against the evolving attacks against e-commerce and its customers. * Unveils the techniques phishers employ that enable them to successfully commit fraudulent acts * Offers an in-depth, high-tech view from both sides of the playing field to this current epidemic * Stay one step ahead of the enemy with all the latest information.